2008
DOI: 10.4103/0378-6323.45100
|View full text |Cite
|
Sign up to set email alerts
|

Role of stressful life events in induction or exacerbation of psoriasis and chronic urticaria

Abstract: Psychological stress plays a significant role in triggering or exacerbating dermatological diseases. Our study indicates the role of relaxation therapies and stress management programs in chronic diseases such as psoriasis and chronic urticaria. Psychological interventions can help individuals to reinterpret events and develop strategies to cope with stressful events, thus decreasing morbidity due to these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 0 publications
3
66
0
4
Order By: Relevance
“…There are reports showing stressful life events, such as loss of close family member, financial problems, major personal illness preceded onset or exacerbation of the disease in a considerable subset of patients with chronic spontaneous urticaria [10,11]. Although many patients report stress to exacerbate their disease, there is a lack of well-controlled studies on this subject [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports showing stressful life events, such as loss of close family member, financial problems, major personal illness preceded onset or exacerbation of the disease in a considerable subset of patients with chronic spontaneous urticaria [10,11]. Although many patients report stress to exacerbate their disease, there is a lack of well-controlled studies on this subject [3].…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic relief with suppression of the pruritus and reduction of the number and size of wheals is the main goal of treatment. Loratadine and cetirizine can be used starting from 6 months of age and are also safe during pregnancy [9,10]. Efficacy of antihistamines is often patient specific and none are consistently superior [16].…”
Section: Antihistaminesmentioning
confidence: 99%
“…12 Stress triggers the symptoms and affects the severity of symptoms in patients with both FM and CU. 13,14 Some pathological changes have been described in the skin biopsies of patients with FM as resembling the cellular and cytokine involvement in the biopsy specimens of patients with CU. [15][16][17][18][19] In addition, it has been suggested that there is an autonomic dysfunction in patients with FM and CU, and sympathomimetic amines may lead to improvement in the symptoms of the two diseases when there is a resistance to conventional therapies.…”
mentioning
confidence: 99%
“…Knowledge of this phenomenon may be useful for professionals who would like to explore psychosocial stressors of chronic skin patients. This is relevant in dermatological care beacuse psychological stress plays an important role in in triggering or exacerbating chronic skin diseases (49). How can attachment styles and attitudes affect patients' consultations with a dermatologist?…”
Section: Discussionmentioning
confidence: 99%
“…Skin diseases can affect patients in their health psychological functioning, e.g. the condition of our skin has an effect on our body image, self-esteem and the way others perceive us (48) Psychological stress plays an important role in in triggering or exacerbating chronic skin diseases (49). In a study arranged by Pärna et al (50) sleep disorder symptoms were the most important form of distress among patients with chronic skin conditions.…”
Section: Psychodermatologymentioning
confidence: 99%